Implementasi Etika Bisnis Islam Dalam Peningkatan Penjualan Di Toko Alat Tulis Kantor Paper One Palembang - Anisa, Sabrina Nur; Zuul Fitriani Umari; Abdullah Sahroni (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study discusses the implementation of Islamic business ethics in increasing sales at the Paper One Stationery Store in Palembang. The background of this research is based on the importance of applying Islamic business ethical values, such as honesty, justice, social responsibility, and compliance with thelaw, in maintaining sustainability and enhancing business image. This study uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation to understand how the application of Islamic business ethics can influence the store‟s sales levels. One of the issues highlighted in this study is the store‟s low rating on Google Reviews, which may affect customer trust and reduce purchase interest. The results show that the implementation of Islamic business ethics at Paper One Store plays an important role in building customer loyalty and improving business reputation. Strategies implemented include improving service quality, price transparency, and a friendly and honest attitude in serving customers. With consistent application of Islamic business ethics, the store can improve its image and increase its competitiveness in the market. This research is expected to serve as a reference for other business actors in adopting theprinciples of Islamic business ethics to support sustainable and blessed business growth.